(untitled) (Journal of Madenat Alelem, 2016)
This study aimed to extract proline acid from locally available plants (Schangina aegyptiaca and Tamaricaceae). The plant was collected from different regions of Baghdad to extract proline acid by two method, first using toluene with ninhydrin, while second using alcohol which was obtained different concentrations (0.192 μ mol /g) for the S. aegyptiacaand (0.302 μ mol /g) for Tamaricaceae,while second method with alcohol obtained (0.811 μ mol /g) from S. aegyptiaca and (0.405 μ mol /g) from Tamaricaceae, which indicated most efficient 50-60% then proline acid was concentrated to (28.6 μ mol /g). The proline concentrations in Schangina aegyptiaca and was higher in Tamaricaceae, therefore proline acid is a natural material adto reduce negative effects of salinity water of irrigation.